Modified Haas Expander for the Treatment of Anterior Openbite and Posterior Crossbite Associated with Thumb Sucking-A Case Report: 3-Years Follow-Up - Nargiz Muradova; Ayça Arman Özçırpıcı (Galenos Yayinevi, 2019)
Thumb sucking is an abnormal habit that occurs in childhood and can cause several malocclusions if it persists for a long time. Malocclusions caused by oral habits require proper treatment timing to maintain a normal growth and should be treated at an early age. This case report shows the management of thumb sucking and early correction of anterior open bite and posterior crossbite by a modified Haas expander. Three-year follow-up results showed the effectiveness of this special designed appliance.